Rancang Bangun Sistem Informasi Arsip Surat Menggunakan Metode Prototype - Masan Abdi Wicaksono; Christ Rudianto; Penidas Fiodinggo Tanaem (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Letters archiving is the process of receiving, collecting, maintaining letters in a structured manner by an agency, however, the process of filing letters at the Unit Pelaksana Teknis Daerah (UPTD) Satuan Pendidikan Non Formal (SPNF) Sanggar Kegiatan Belajar (SKB) Salatiga still has problems such as recording letter archive data that still uses a letter agenda book which sometimes occurs errors in recording, archival document storage which is physically stored on a mailing cabinet which is prone to being lost, scattered, or damaged and the large number of existing documents causes employees to need extra time and effort to look for them. With the Letter Archive Information System designed using the prototype method, it allows employees to take part in the design of this system by providing opinions and suggestions on system design so that the results will be more optimal, maximum and can be a solution to the problems that exist in the Unit Pelaksana Teknis Daerah (UPTD) Satuan Pendidikan Non Formal (SPNF) Sanggar Kegiatan Belajar (SKB) Salatiga.